2015
DOI: 10.3109/14756366.2015.1094468
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of guanylhydrazones as potential inhibitors or reactivators of acetylcholinesterase

Abstract: Analogs of pralidoxime, which is a commercial antidote for intoxication from neurotoxic organophosphorus compounds, were designed, synthesized, characterized, and tested as potential inhibitors or reactivators of acetylcholinesterase (AChE) using the Ellman's test, nuclear magnetic resonance, and molecular modeling. These analogs include 1-methylpyridine-2-carboxaldehyde hydrazone, 1-methylpyridine-2-carboxaldehyde guanylhydrazone, and six other guanylhydrazones obtained from different benzaldehydes. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In previous studies by our research group using molecular modeling and inhibition tests it has been found that the cationic site of guanylhydrazones are appropriate to interact with the anionic region of the AChE active site and compete with acetylcholine. 39,40 For this reason, a new guanylhydrazone (2) having some structural similarity with tacrine was prepared. Its guanidine group, a cationic group, can interact with the anionic site of the active site of the enzyme, and NMR results showed that this new guanylhydrazone is a more efficient inhibitor than tacrine.…”
Section: Chemistrymentioning
confidence: 99%
“…In previous studies by our research group using molecular modeling and inhibition tests it has been found that the cationic site of guanylhydrazones are appropriate to interact with the anionic region of the AChE active site and compete with acetylcholine. 39,40 For this reason, a new guanylhydrazone (2) having some structural similarity with tacrine was prepared. Its guanidine group, a cationic group, can interact with the anionic site of the active site of the enzyme, and NMR results showed that this new guanylhydrazone is a more efficient inhibitor than tacrine.…”
Section: Chemistrymentioning
confidence: 99%
“…To determine the capacities of these compounds to interact with HuAChE, docking was performed, 23 and the percentage inhibition of HuAChE was determined using Fig-NMR. 24,25 The toxicity was assessed in vivo using mice. 26,27 Concerning the synthesis, the reaction of 3-methoxy-2hydroxybenzaldehyde (1) and dimedone (2) afforded two possible compounds, 3 and 4, as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…To experimentally conrm that compounds 5, 6 and 7 can inhibit HuAChE in vitro, the Fig-NMR method was performed, as described in two prior articles published by our research group. 24,25 The 1 H NMR spectrum of a solution containing pure AChE in the presence of ACh was recorded every 5 minutes for 110 minutes, providing 22 spectra. By looking at the relative amounts of ACh and its decomposition product, acetic acid, in the resultant spectra, it was possible to asses the ability of AChE to decompose ACh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylcholinesterase (AChE, EC. 3.1.1.7) is a crucial enzyme used to control transmission between neurons when the process is either mediated or modulated by the neurotransmitter acetylcholine (ACh) [64][65][66][67] . ACh is released by the axon terminal or varicosities of the transmitter neuron into the extracellular space to interact with the receptors of the other neuron.…”
Section: Introductionmentioning
confidence: 99%